The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.macromol.0c00598
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Block Sequence in All-Conjugated Triblock Copoly(3-alkylthiophene)s on Control of the Crystallization and Field-Effect Mobility

Abstract: Despite recent impressive advances in synthesis of all-conjugated diblock copolymers via facile quasi-living Grignard metathesis (GRIM) polymerization, it remains challenging to achieve well-defined all-conjugated triblock copolymers of interest. Herein, we report the judicious design and synthesis of a series of all-conjugated triblock copoly­(3-alkylthiophene)­s consisting of poly­(3-butylthiophene) (P3BT), poly­(3-hexylthiophene) (P3HT), poly­(3-octylthiophene) (P3OT), or poly­(3-dodecylthiophene) (P3DDT) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Recently, we have reported reversible phase transition between forms I and II in P3HS thin films treated by alternating thermal and solvent vapor annealing and the cocrystals of poly­(3-butylhexylthiophene)- block -poly­(3-hexylselenophene) (P3BT- b -P3HS) for high-performance organic field-effect transistors (OFETs). Furthermore, we have extended the cocrystals to triblock copoly­(3-alkylthiophene)­s and explored the effect of block sequence on their crystalline and charge transport behavior . However, as an important member in the P3AS family, the relation between crystalline structures of poly­(3-butylselenophene) (P3BS) and their charge transport properties has not yet been reported due to its synthesis difficulty and poor solubility in common organic solvents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have reported reversible phase transition between forms I and II in P3HS thin films treated by alternating thermal and solvent vapor annealing and the cocrystals of poly­(3-butylhexylthiophene)- block -poly­(3-hexylselenophene) (P3BT- b -P3HS) for high-performance organic field-effect transistors (OFETs). Furthermore, we have extended the cocrystals to triblock copoly­(3-alkylthiophene)­s and explored the effect of block sequence on their crystalline and charge transport behavior . However, as an important member in the P3AS family, the relation between crystalline structures of poly­(3-butylselenophene) (P3BS) and their charge transport properties has not yet been reported due to its synthesis difficulty and poor solubility in common organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we have extended the cocrystals to triblock copoly(3-alkylthiophene)s and explored the effect of block sequence on their crystalline and charge transport behavior. 28 However, as an important member in the P3AS family, the relation between crystalline structures of poly(3-butylselenophene) (P3BS) and their charge transport properties has not yet been reported due to its synthesis difficulty and poor solubility in common organic solvents. Thus, it is challenging to do film deposition for the fabrication of thin film devices.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It was found that the stability of the triblock copolymers under visible light irradiation at ambient temperature was improved by the addition of PANi block [127]. It was also reported by the previous literature that the triblock copolymer has better control of the on-chain orientation and thus is able to give an improvement in the produced conjugated polymers properties [60]. Table 7 summarizes the advantages and disadvantages of the copolymerization and blending methods.…”
mentioning
confidence: 79%
“…An acid dopant is usually used during the synthesis of PANi to improve its conductivity. One of the most common dopants used is hydrochloric acid (HCl) [60,61]. Sulphuric acid (H 2 SO 4 ) is another acid dopant that is used as an alternative to HCl in the PANi synthesis.…”
Section: Acid Dopants For Pani Synthesismentioning
confidence: 99%
“…Many rod-coil block copolymers that consist of P3HT are reported to exhibit good optoelectronic properties. Rod-coil diblock and triblock copolymers with P3HT were synthesized using Grignard metathesis polymerization (GRIM) and other living polymerization techniques. The synthesis of rod-rod block copolymers with P3HT was performed by attaching a liquid crystalline block to P3HT. There are a few recent reports based on the synthesis of all conjugated block copolymers based on P3HT or a block copolymer with liquid crystalline blocks attached to P3HT. , Stefan’s group reported P3HT block copolymers comprising poly­(γ-benzyl- l -glutamate) and poly­( N -hexylisocyanate). , In another report, Lin and co-workers had demonstrated the synthesis of a P3HT- b -poly­(3-butylthiophene) diblock copolymer with greatly improved crystallinity and electrical conductivity upon solvent annealing .…”
Section: Introductionmentioning
confidence: 99%